O DIREITO FUNDAMENTAL À ALIMENTAÇÃO NOS TRIBUNAIS - Maria Célia Delduque; Alessandra Barreto da Silva (Universidade do Estado do Rio de Janeiro, 2014)
The legalization of public health policies has been addressing an increasingly comprehensive list of lawsuits and services, particularly in the realm of Human Right to Food. In view of this context, this research study aimed to examine and analyze lawsuits over the Human Right to Food filed in courts of five Brazilian regions. The research used primary data collected from copies of court proceedings. The period of analysis ranged between 2005 and 2008. The objective was to gather information on lawsuits resolved through transit in rem judicatam in a court of first instance. There were  62 requests for special dietary supplements, with particularly more cases in the southeastern region of the country. The plaintiffs were mostly children with different pathologies declared in the records, and no collective lawsuits were found in the sample. The study showed no evidence of prescriptions given by professional nutritionists or expert examinations requested by the judges. There were judgments made solely upon medical prescriptions. From the total court decisions analyzed, 91.77% of the decisions were favorable to the plaintiff and 8.33% of the decisions were unfavorable to the complaint. It was concluded that there is a strong growth trend of lawsuits on the issue of right to food because it is  guaranteed by the Constitution. DOI: http://dx.doi.org/10.12957/demetra.2014.10213